Traditional Institutions Meet the Modern World: Caste, Gender, and Schooling Choice in a Globalizing Economy - Munshi, Kaivan; Rosenzweig, Mark (American Economic Review, 2006)
This paper addresses the question of how traditional institutions interact with the forces of globalization to shape the economic mobility and welfare of particular groups of individuals in the new economy. We explore the role of one such traditional institution—the caste system—in shaping career choices by gender in Bombay using new survey data on school enrollment and income over the past 20 years. We find that male working-class—lower-caste—networks continue to channel boys into local language schools that lead to the traditional occupation, despite the fact that returns to nontraditional white-collar occupations rose substantially in the 1990s, suggesting the possibility of a dynamic inefficiency. In contrast, lower-caste girls, who historically had low labor market participation rates and so did not benefit from the network, are taking full advantage of the opportunities that became available in the new economy by switching rapidly to English schools.